Informal Leadership Patterns in Local Bureaucracy: Implications for Policy Responsiveness in Bandung Regency, Indonesia - Ednawan Prihana (Sakura Digital Nusantara, 2026)
Purpose: This study aims to analyze the role of informal leadership in influencing policy responsiveness within the local bureaucracy of Bandung Regency, Indonesia. The study focuses on understanding how informal leadership patterns emerge and how they affect bureaucratic decision-making and public policy responsiveness. Methods: This research used a qualitative case study approach. Data were collected through in-depth interviews with 25 informants consisting of government officials, bureaucratic staff, community leaders, NGO representatives, and local residents. Focus group discussions and policy document analysis were also conducted to support the data. The data were analyzed using thematic analysis with source and method triangulation to ensure validity. Findings: The results show that informal leadership develops through personal charisma, close relationships with the community, and political patronage networks. These informal leadership patterns help accelerate coordination and improve communication between the government and society, which supports faster policy responses. However, the findings also indicate several negative impacts, such as dependence on certain individuals, unequal access to influence, and potential bias in decision-making processes. Research Implications: The findings indicate the importance of understanding informal leadership dynamics in local governance. Local governments need to strengthen institutional transparency and accountability while maintaining constructive relationships with informal actors in policy processes. Originality: This study provides empirical evidence on how informal leadership operates within local bureaucracy in Bandung Regency. The study also highlights the dual role of informal leadership as both a supporting and limiting factor in bureaucratic responsiveness within decentralized governance. Conclusions: Informal leadership has an important role in increasing policy responsiveness in local bureaucracy, particularly in accelerating coordination and strengthening social legitimacy. Nevertheless, stronger institutional control is needed to minimize the risks of political bias and unequal policy representation.